Faktor gaya hidup yang berhubungan dengan indeks massa tubuh mahasiswa Universitas Muhammadiyah Aceh - Edi Ardiansyah; Asnawi Abdullah; Fauzi Ali Amin (Jurnal SAGO Gizi dan Kesehatan, 2026)
Background: Obesity has become an increasing public health problem, including among Indonesian university students. Lifestyle changes, particularly low physical activity and high fast-food consumption, are suspected to contribute to an increased body mass index (BMI) among students.Objective: This study aimed to analyze the factors associated with body mass index (BMI) among Universitas Muhammadiyah Aceh students.Methods: This study employed an analytical observational design with a cross-sectional approach and was conducted in August 2019. A total of 94 students were selected using proportional sampling methods. Data were collected through structured interviews and anthropometric measurements of the participants. Bivariate analysis was performed using the chi-squared test, followed by multivariate analysis using logistic regression to identify the determinant factors associated with BMI.Results: Most respondents had a normal nutritional status (62.77%), followed by overweight (17.02%) and obese (20.21%) statuses. Fast food consumption, snacking habits, screen-viewing duration, physical activity, nutritional knowledge, food promotion exposure, and use of food delivery services were significantly associated with body mass index (p<0.05). Low physical activity was the strongest determinant, increasing the risk of obesity by 12.84 times, followed by frequent fast food consumption, which increased the risk by 7.62 times.Conclusion: Low physical activity and high fast-food consumption were the main factors associated with increased BMI in university students. Campus-based interventions focusing on physical activity promotion, practical nutrition education, and improvement of the campus food environment are recommended to prevent obesity in students.